The long-run behaviour of the terms of trade between primary commodities and manufactures: A panel data approach - Jesús Otero; Ana María Iregui (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
This study examines the Prebisch and Singer hypothesis using a panel of 24 commodity prices from 1900 to 2010. The modelling approach stems from the need to meet two key concerns: (1) the presence of cross-sectional dependence among commodity prices; and (2) the identification of potential structural breaks. To address these concerns, the Hadri and Rao test (2008) is employed. The findings suggest that all commodity prices exhibit a structural break at different locations across series, and that support for the Prebisch and Singer hypothesis is mixed. Once the breaks are removed from the underlying series, the persistence of commodity price shocks is shorter than that obtained in other studies using alternative methodologies.
Keywords: O13; C33; 330; Prebisch and Singer hypothesis; panel stationarity; Terms of Trade; Rohstoffpreis